IMPLEMENTASI E-GOVERNMENT DALAM PEMANFAATAN APLIKASI MOBILE PASPOR (M-PASPOR) PADA KANTOR IMIGRASI KELAS II TPI TANJUNG UBAN - Riski Peni Wulandari; Novi Winarti; Eki Darmawan (PT. Jurnal Center Indonesia Publisher, 2024)
M-Paspor aims to make passport services more transparent, accountable and fast. However, in the process of its application as a public servant, the socialization provided has not been able to fully reach the community. So people have to come repeatedly to just ask questions related to the use of the application. This study aims to describe the implementation of e-government in the use of m-paspor applications at the Immigration Office Class II TPI Tanjung Uban. The research method used is a qualitative method with a descriptive approach. The theory used from Harvard JFK School of Government, with several indicators including Support, Capacity and Value. The results showed that the implementation of e-government in the use of m-paspor applications has run in accordance with the objectives but has not been optimal in one of the indicators. In the Support indicator, support in the form of SOP’s and m-paspor policies, direct socialization and through social media as well as supporting infrastructure at the Immigration Office Class II TPI Tanjung Uban is quite good. In the Capacity indicator, the availability of financial resources is intended for socialization needs, the information technology infrastructure in the service process looks adequate to facilitate the community, but in the process of implementing the application there are still several obstacles, including frequent application errors, payment codes do not come out, limited quotas and so on, as well as the availability of human resources derived from receiving CPNS selection analysis S1 immigration and has been provided with periodic training by the Directorate General of Immigration. The Value indicator is considered good, because both officers and the public have been able to feel the convenience with the m-paspor application.